2013
DOI: 10.1080/09540121.2013.855301
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical factors correlating with high levels of psychological distress in HIV-positive women living in Ontario, Canada

Abstract: The concept of psychological distress includes a range of emotional states with symptoms of depression and anxiety and has yet to be reported in HIV-positive women living in Ontario, Canada, who are known to live with contributing factors. This study aimed to determine the prevalence, severity, and correlates of psychological distress among women accessing HIV care participating in the Ontario HIV Treatment Network Cohort Study using the Kessler Psychological Distress Scale (K10). The K10 is a 10-item, five-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
4
10
1
Order By: Relevance
“…This result confirms the increased vulnerability to psychological distress among MLHIV (Benoit et al, 2014;Brackis-Cott, Mellins, Dolezal, & Spiegel, 2007;Catz, Gore-Felton, & McClure, 2002). This high prevalence cuts across sociodemographic characteristics and cannot be explained by low socioeconomic position, immigration status, or time since HIV diagnostic.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This result confirms the increased vulnerability to psychological distress among MLHIV (Benoit et al, 2014;Brackis-Cott, Mellins, Dolezal, & Spiegel, 2007;Catz, Gore-Felton, & McClure, 2002). This high prevalence cuts across sociodemographic characteristics and cannot be explained by low socioeconomic position, immigration status, or time since HIV diagnostic.…”
Section: Discussionsupporting
confidence: 89%
“…While medical care is covered by insurance in Quebec, financial challenges can impair access to HIV medication because of the deductible of insurance companies which compels MLHIV to prioritize between their differing needs. These factors were associated with clinical psychological distress, supporting previous conclusions linking financial strain to psychological distress among PLHIV (Barsky & Albertini, 2006;Benoit et al, 2014;Cunningham et al, 1999;Moneyham et al, 2010;Reif et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, another study has shown increased CD8+ T lymphocyte counts associating with symptoms of depression and anxiety [29]. By contrast, elevated symptoms of anxiety were associated with a higher CD4 count in one study [32], while others reported no associations between severity of self-reported affective symptoms or disorders and CD4 count [22, 33, 34]. The considerable individual, psychosocial, and disease-related heterogeneity of participants may add to the mixed findings in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been some consistency showing an association between better mental health and having a stable partner (Protopopescu et al, 2007), having higher education (Benoit et al, 2014;Murri et al, 2003) and having employment (Blalock, McDaniel, & Farber, 2002;Rueda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%